Epidemiological analysis of leprosy in Brazil from 2016 to 2020 (Research, Society and Development, 2022)
Introduction: Leprosy is a chronic infectious disease related to social and economic factors, still very present in Brazil Objective: This study aimed to outline the epidemiological profile of leprosy in Brazil between 2016 and 2020.Methods: This is a descriptive, retrospective epidemiological study with a quantitative approach. Data were obtained by consulting the Department of Informatics of the Unified Health System (DATASUS). Results: Leprosy is still a public health problem in the country, as Brazil is the most responsible for cases of the disease in Latin America, with the Northeast, North and Midwest regions standing out as the main producers of new cases. In addition, males are the most affected by the disease, as they develop a lower immune response when compared to females, mainly affecting economically active individuals. In addition, the lack of access to information and socioeconomic precariousness are factors that increase the lack of treatment and the spread of the disease, with emphasis on its multibacillary form. Conclusion: The need to develop a plan that encourages early detection is clear. and the reduction of incapacities caused by the disease, through health surveillance actions, aimed at combating it. Furthermore, it is extremely important to adapt the leprosy care policy to the reality of regions where the incidence is higher, to increase adherence to treatment and, consequently, eradicate the disease.